Prevalence and prognostic value of baseline and post-treatment renal insufficiency in colorectal cancer patients: a large retrospective cohort study of 10,581 patients in Shanghai, China (2019–2023) - Li, Juan; Bai, Chen Guang; Liu, Baoshuai; Pan, Shouyu; Liu, Lianjie; Jiang, Jianjun; Lu, Jian; Cao, Guangwen; Zhang, Wei; Gao, Xian Hua (Frontiers in Medicine, 2026)
BackgroundBaseline renal insufficiency (RI) and post-treatment renal insufficiency (PTRI) are prevalent comorbidities in patients with colorectal cancer (CRC). However, the prevalence, risk factors, and prognostic significance of these conditions remain controversial.MethodsThis is a retrospective cohort study, which included all CRC patients treated at Shanghai Changhai Hospital (2019–2023). Multivariate logistic and Cox survival analyses were used to explore risk factors and prognostic value of baseline RI and PTRI.ResultsAmong 10,581 CRC patients, the prevalence rates of RI-related parameters were: baseline RI (32.4%), hematuria (31.2%), elevated serum cystatin C (CysC) (17.4%), proteinuria (12.3%), elevated serum uric acid (8.7%), elevated serum creatinine (4.3%), elevated blood urea nitrogen (BUN) (3.5%), reduced estimated glomerular filtration rate (eGFR) (2.2%), chronic kidney disease (CKD) diagnosed by ultrasonography(1.5%), and self-reported CKD (1.1%). Approximately half of RI cases (47.2%) were attributed to hematuria, and other RI-related parameters were complementary to hematuria in revealing RI. Among the 2,132 (20.3%) patients with PTRI, 14.8, 8.3, 4.4, 3.9 and 0.2% exhibited a ≥ 25% alteration in BUN, CysC, creatinine, eGFR and UA, respectively. Age ≥ 65 years and concomitant cardiovascular disease were independent predictors of baseline RI; open surgery, intestinal ostomy, postoperative complications and chemoradiotherapy were independent predictors of PTRI. Both baseline RI and PTRI were independent predictors of disease-free survival and overall survival.ConclusionThese results demonstrate that comprehensive RI assessment (incorporating eGFR, hematuria, proteinuria, and other RI-related parameters) provides clinically actionable insights. Given the high prevalence (baseline RI 32.4%, PTRI 20.3%) and significant survival impacts, early screening of RI and preventive strategies are critical for high-risk CRC patients.